Risk factors of undernutrition among under-two children in West Java (SSGI 2021) - Batubara, Fithriani; Dwiriani, Cesilia Meti; Riyadi, Hadi (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2024)
ABSTRAK Latar Belakang: Jawa Barat merupakan provinsi dengan jumlah populasi balita tertinggi di Indonesia. Permasalahan gizi di Jawa Barat masih tinggi. Berdasarkan Studi Status Gizi Indonesia (SSGI) tahun 2021 prevalensi stunting, wasting dan underweight di Jawa Barat yaitu 20.5%. 5.3% dan 15%. Faktor risiko yang mempengaruhi kekurangan gizi beragam dan berpotensi berubah dari waktu ke waktu. Oleh karena itu, sangat penting untuk menilai arus status gizi untuk meninjau kesenjangan dalam faktor risiko.Tujuan: Penelitian ini dilakukan untuk menganalisis faktor risiko stunting, wasting, dan underweight pada baduta di Jawa Barat. Metode: Penelitian ini menggunakan studi cross sectional menggunakan data sekunder dari Studi Status Gizi Indonesia (SSGI) 2021 yang terdiri dari 1203 subjek baduta usia 6-23 bulan di Jawa Barat. Faktor risiko stunting, wasting, dan underweight dianalisis menggunakan regresi logistik. Hasil: Prevalensi stunting, wasting, dan underweight pada baduta usia 6-23 bulan berturut-turut sebesar 20.5%, 5.7% dan 11.6%. Faktor risiko stunting adalah usia 12-23 bulan (AOR=3.10 CI 95% 2.16-4.45), panjang lahir pendek (AOR=1.85 CI 95% 1.30-2.62), tingkat pendidikan ibu rendah (AOR=1.97 CI 95% 1.45-2.68) dan tidak menyusui (AOR= 0.46 CI 95% 0.31-0.68) sebagai faktor protektif. Faktor risiko wasting adalah tingkat pendidikan Ibu yang rendah (AOR=0.5 CI 95% 0.34-0.94) sebagai faktor protektif. Faktor risiko underweight adalah usia 12-23 bulan (OR=1.92 CI 95% 1.25-2.95) dan tidak ASI eksklusif (AOR=0.54 CI 95% 0.35-0.83) sebagai faktor protektif. Kesimpulan: Faktor yang memengaruhi stunting yaitu usia, panjang lahir, tingkat pendidikan ibu, dan status menyusui. Faktor yang memengaruhi wasting yaitu tingkat pendidikan ibu. Faktor yang memengaruhi underweight yaitu usia dan riwayat ASI eksklusif. KATA KUNCI: baduta; faktor risiko; gizi kurang; Jawa Barat; SSGI ABSTRACTBackground: West Java is the province with the highest under-five population in Indonesia. Nutritional problems in West Java are still high in number. According to the 2021 Indonesian Nutrition Status Study (SSGI) the prevalence of stunting, wasting and underweight in West Java are stated as 20.5%. 5.3% and 15% whereas the risk factors affecting malnutrition are diverse and have the potential to change over time. Therefore, it is very important to assess current nutritional status to review gaps in risk factors. Objectives: This research was conducted to analyze the risk factors for stunting, wasting and underweight in under-two children of West Java. Methods: This research is a cross-sectional study using secondary data from the Indonesian Nutrition Status Study (SSGI) 2021 which consists of 1203 subjects (6-23 months) in West Java. Risk factors of stunting, wasting. and underweight were analyzed using logistic regression. Results: The prevalence of stunting, wasting and underweight among children aged 6-23 months were 20.5%, 5.7% and 11.6%, respectively. The risk factors for stunting are age 12-23 months (AOR=3.10 CI 95% 2.16-4.45), short birth length (AOR=1.85 CI 95% 1.30-2.62), mother’s low education level (AOR=1.97 CI 95% 1.45-2.68) and not breastfeeding (AOR= 0.46 CI 95% 0.31-0.68) as a protective factor for stunting. low maternal education level (AOR=0.5 CI 95% 0.34-0.94) as a protective factor for wasting. The risk factor for underweight is age 12-23 months (OR=1.92 95% CI 1.25 -2.95) and does not have exclusively breastfed (AOR=0.54 CI 95% 0.35-0.83) as a protective factor for underweight. Conclusions: Influential factors to stunting are age, birth length, mother's education level, and breastfeeding status. Factor influences wasting is the education level of the mother. Factors influence underweight are age and history of exclusive breastfeeding. KEYWORDS: risk factors; SSGI; undernutrition; under-two children; West Java